Community Engagement and Adaptive Regulation in Sustainable Urban Change: Assessing New Jersey’s Cumulative Impacts Program - Pitcock, Grayson (European Journal of Sustainable Development, 2025)
Cumulative impact assessment has been widely endorsed by governments, scientists, community organizations and environmental groups as an important framework for addressing environmental injustice in communities that are overburdened with multiple sources of pollution. In 2020, the first state cumulative impact legislation within the United States was passed in New Jersey, which has served as a potential model for other states and cities. Finalized in April 2023, New Jersey’s cumulative impacts regulations adopt a community-engagement approach before approving permits for major pollution-generating facilities and uses a community-level mapping tool providing localized environmental and public health data to enable cumulative impacts assessment. Through a case study of this regulatory program, the paper will assess the legislative and regulatory program’s strengths and weaknesses in achieving overall reductions in pollution levels within overburdened communities in furtherance of Sustainability Goal 10. The purpose of the study is to provide guidance to other states and cities also seeking to adopt cumulative impact programs. Keywords: Environmental Justice, Cumulative Impact Assessment, Sustainable Urbanism